Solid-state characterization and dissolution properties of Fluvastatin sodium salt hydrates - Borgmann, Silvia H. M. (2012)
The present study reports the solid-state properties of Fluvastatin sodium salt crystallized from different solvents for comparison with crystalline forms of the commercially available raw material and United States Pharmacopeia (USP) reference standard. FLV samples were characterized by several techniques; such as X-ray powder diffractometry, differential scanning calorimetry, thermogravimetry, liquid and solid-state nuclear magnetic resonance spectroscopy, diffuse reflectance infrared Fourier transform spectroscopy, and scanning electron microscopy. In addition, intrinsic dissolution rate (IDR) of samples was performed in order to study the influence of crystalline form and other factors on rate and extent of dissolution. Three different forms were found. The commercial raw material and FluvastatinACN were identified as “form I” hydrate, the USP reference standard as “form II” hydrate and an ethanol solvate which presented a mixture of phases. Form I, with water content of 4%, was identified as monohydrate.